На дальнем Западе - Сальгари Эмилио (Библиотека "Вокруг света", 1992)
Экземпляры: ф.10 (1993) / Инвентарный номер: 37148 / Цена: / Сис.шифр: 84(4Ита)-4 / Авт.знак: С 16 / ГРНТИ: 17.82.31 / ББК: 84(4Ита)-44